(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Cognitive linguistics is a modern approach to the study of language that emphasizes the relationship between language and the human mind. It investigates how language reflects mental processes, conceptual structures, and embodied experience. This article provides an overview of the key principles, history, and core areas of study within cognitive linguistics, focusing on its relevance to language structure, meaning, metaphor, and categorization.